Best Practicable Environmental Option (BPEO) for decommissioned offshore platforms - Samsudin, Nurhayaty (IRC, 2015)
A large number of offshore platforms in Malaysia are reaching their design life. According to the international regulations, platforms that have reached their design life should be decommissioned. However, decommissioning requires an extensive planning before it can be carried out since the costs involved can amount to billions. Over the years, various tools and methods have been developed in order to assist in the planning for decommissioning activities. One of the methods that have been widely used in the industry is Best Practicable Environmental Option or BPEO method. In the decision-making phase of decommissioning, various stakeholders are involved including the client (operator company) as well as related regulatory bodies such as Fisheries Department and the Department of Environment. However, the current practice in the industry mainly focuses on the interests of the clients and barely considering the interests of other stakeholders. Therefore, the main objective of this study is to produce a sustainable model for BPEO which will consider the interests of all stakeholders involved in the process of decommissioning. The scope of this study entails the BPEO method as a sustainable framework for decommissioning of offshore platforms. Several scenario will be tested for two stakeholders and the observations will be used to model an equation that balances the interest of each party thus providing a sustainable model for BPEO.